Knowledge Management in Chile: An Analysis of 10 Years of Initiatives in the Public and Private Sector - Perez-Arrau, J (Academic Conferences and Publishing International Limited, 2022)
Knowledge management is a discipline that seeks to rationalize the use of knowledge and information in organizations. Since its origins in the nineties, it has developed mainly in countries of the global north, with few contributions from and to developing countries, such as Chile. In recent years, concept of knowledge management in Chile has been used increasingly within economic, administrative, and business environments. However, despite these advances, the scarce existing research in this field does not allow us to clearly visualize the state of development of these initiatives, their characteristics, or their results. Consequently, this study seeks to contribute to the understanding of this new area of development for organizations through the qualitative analysis of twenty-four cases of knowledge management initiatives carried out in public and private organizations in Chile, between 2010 and 2020. It describes the motivations that originated the initiatives, the tools used, some of the difficulties encountered, and other aspects of interest for disciplinary development. Finally, the article concludes with an analysis of the state of development of knowledge management in Chile and a proposed typology to situate the state of progress of organizations in this area. © 2022, Academic Conferences and Publishing International Limited. All rights reserved.